Sub-humanising The Others: Cross-Cultural Reception of Films. , Iranian/Western Interpretation of Snyder’s 300 (Raparin Journal of Humanities (RJH), 2020)
This paper aims to scrutinizes the reception of 300 film (Dir: Snyder, 2007). Debunking the concepts of “immanent meaning”, “autonomous of the text” and other hermeneutics-based interpretations of text, has been renounced for marginalizing the audiences.Within the realm of Reception theory and audience research as audiences are understood to be engaged in a process of making, rather than simply absorbing, meanings; this paper takes an approach of analyzing the cross-cultural making meaning of 300 by looking at Iranian/western interpretation of the film and investigating the data: comments and reviews from weblogs and internet forums as well as the encounter between audiences via Youtube, which have been established anti/pro of the film.Firstly, this paper interrogates the synchronic area of film [film production, distribution, exhibition and journalistic review, and social and historical contexts like economy, law, religion, politics, class, race and ethnicity gender etc] as well as   the diachronic areas [academic theory, criticism and history, broadcasting, satellite and cable television, fan culture, the biographical legend and cross-cultural reception. [Klinger, 1997]. Secondly, how the contextual influence on the textual, more precisely how the film has been linked to the political conflict between United Stated and Iran, during the its ‘War on Terror’ in Middle East. Lastly, due to authorial restrictions and media monitoring on the film in Iran only a few number of Iranian audiences likely to have seen the film. The method of data analysis is based on viewer’s responses to a BBC news report uploaded in Youtube about the political controversy between Iran and US on the film.  As well as analysing the Iranian diasporas’ E-protesting by establishing website and weblogs against the film.